Safety and efficacy of double plasma molecular adsorption system with sequential low‐volume plasma exchange in intermediate‐stage hepatitis B virus‐related acute‐on‐chronic liver failure. Issue 3 (20th March 2023) - Xu, Wenxiong; Zhu, Shu; Yang, Luo; Li, Zhipeng; Wu, Lina; Zhang, Yeqiong; Chen, Jia; Deng, Zhexuan; Luo, Qiumin; Peng, Liang
Abstract: Current evidence suggests that the mortality rate of intermediate‐stage hepatitis B virus (HBV)‐related acute‐on‐chronic liver failure (ACLF) remains high. We aimed to investigate the safety and efficacy of double plasma molecular adsorption system (DPMAS) with sequential low‐volume plasma exchange (LPE) treatment in intermediate‐stage HBV‐related ACLF. This prospective study recruited intermediate‐stage HBV‐related ACLF patients and was registered on ClinicalTrials.gov (NCT 04597164). Eligible patients were randomly divided into a trial group and a control group. Patients in both groups received comprehensive medical treatment. Patients in the trial group further received DPMAS with sequential LPE. Data were recorded from baseline to Week 12. Fifty patients with intermediate‐stage HBV‐related ACLF were included in this study. The incidence of bleeding events and allergic reactions in the trial group was 12% and 4%, respectively, with no other treatment‐related adverse events. The levels of total bilirubin and prothrombin time‐international normalized ratio, and model for end‐stage liver disease scores after each session of DPMAS with sequential LPE were significantly lower than those before treatment (all p  < 0.05). The 12‐week cumulative liver transplantation‐free survival rates in the trial and control groups were 52% and 24%, respectively ( p  = 0.041). The 12‐week cumulative overall survival rates in the trial and control groups were 64% and 36%, respectively ( p  = 0.048). The Kaplan–Meier survival analysis revealed significant differences in liver transplantation‐free survival ( p  = 0.047) and overall survival ( p  = 0.038) between the trial and control groups. Cox regression analysis indicated that blood urea nitrogen ( p  = 0.038), DPMAS with sequential LPE ( p  = 0.048), and Chinese Group on the Study of Severe Hepatitis B‐ACLF II score ( p  < 0.001) were significant risk factors for mortality. DPMAS with sequential LPE treatment is safe and effective for patients with intermediate‐stage HBV‐related ACLF.